2018
DOI: 10.1002/joc.5734
|View full text |Cite
|
Sign up to set email alerts
|

Moisture transport associated with large precipitation events in the Upper Colorado River Basin

Abstract: Interannual streamflow variability poses numerous water supply forecasting and management challenges for mountain snowpack‐sourced basins across the western United States. Previous studies have shown that substantial proportions of annual precipitation occur during relatively few large precipitation events (LPEs) and consequently, such events tend to be significant predictors of streamflow for many basins, including the Upper Colorado River Basin (UCRB). While some primary pathways of atmospheric moisture tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Dettinger et al, 2011;Ralph et al, 2006). Two main trajectories have been identified for the large precipitation event incursions into the UCRB: one involves flow from the southwest, drawing the Pacific moisture into the southern section of the UCRB; the other follows flow from the west, advecting Pacific moisture into the northern section of the UCRB (Alexander et al, 2015;Kirk and Schmidlin, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…Dettinger et al, 2011;Ralph et al, 2006). Two main trajectories have been identified for the large precipitation event incursions into the UCRB: one involves flow from the southwest, drawing the Pacific moisture into the southern section of the UCRB; the other follows flow from the west, advecting Pacific moisture into the northern section of the UCRB (Alexander et al, 2015;Kirk and Schmidlin, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…(2017) found that strong ridge patterns along with similar dry patterns have been increasingly common in the spring and early summer, contributing to the early 21st century drought across western North America including the UCRB. Several hypotheses have been proposed to elaborate the dynamical mechanisms of the enhanced likelihood of ridge frequency and persistency over the western United States (Burgdorf et al., 2019; Kirk & Schmidlin, 2018; Namias, 1983). One of them argues that the Arctic amplification because of rapid Arctic warming contributes to slower zonal propagation of weather patterns, which is attributable to weakened zonal winds, allowing ridges lingering over certain regions for longer time (Francis & Vavrus, 2015; Kirk & Schmidlin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed to elaborate the dynamical mechanisms of the enhanced likelihood of ridge frequency and persistency over the western United States (Burgdorf et al., 2019; Kirk & Schmidlin, 2018; Namias, 1983). One of them argues that the Arctic amplification because of rapid Arctic warming contributes to slower zonal propagation of weather patterns, which is attributable to weakened zonal winds, allowing ridges lingering over certain regions for longer time (Francis & Vavrus, 2015; Kirk & Schmidlin, 2018). In addition, the reduced zonal winds in the midlatitude may result in less contributions from orographic lift to precipitation production in the western United States.…”
Section: Discussionmentioning
confidence: 99%
“…In the UCRB, most mountain ranges are oriented north-south, creating a physical barrier and enhancing orographic lift (air is forced to rise and subsequently cool). As a result, the condensation increases, leading to increased precipitation rates in a given storm event on the windward mountainside [67]. The basin has consistently high monthly precipitation in the winter season (November-April), where 50$ of precipitation falls as snow [63,68].…”
Section: Study Sitementioning
confidence: 99%